Remarkable Hematological Laboratory Findings in Patients with Fibromyalgia Syndrome - Selçuk Sayılır (Galenos Yayinevi, 2016)
Objective: In our study, we examined the role of mean platelet volume (MPV) and red blood cell distribution width (RDW) values with certain laboratory findings in Fibromyalgia syndrome (FMS). This study is the first study which evaluates the relationship between MPV and RDW values in FMS patients. Materials and Methods: The study consisted of two groups; study group (n=36; FMS patients) and control group (n=36). Patients not having hypertension, hypercholesterolaemia or diabetes, chronic inflammatory disease, history of thrombotic disease or not receiving anticoagulant agents, and as well as patients having body mass index of <30 kg/m2 were included in the study. Data were examined via computer-based software programs, retrospectively. Results: The study population consisted of 36 female FMS patients and 36 female control individuals. The mean ages of the patients in FMS and control groups were 44.6 years 42.5 years, respectively. There were not significant statistical differences between the groups in terms of hemoglobin levels, hematocrit levels, mean erythrocyte volume, platelet count, and RDW and MPV values. On the other hand, the RDW values were found to be statistically significant between the groups. Conclusion: The present study demonstrated that MPV levels were not significantly higher between the groups; however, statistically significant values of RDW might be considered in clinical practice.